[RETRACTED] The Legal Aspect of the Tax Competition in EU: Case of Kosovo - Morina, Fitore Gezim (Muhammadiyah University Press, 2018)
The article entitled The Legal Aspect of the Tax Competition in EU: Case of Kosovodilakan REVOCATION (RETRACTED) from Journal of Jurisprudence Vol 8, No. 2 (2018): Vol 8, No 2, December 2018 at http://journals.ums.ac .id / index.php / jurisprudence / article / view / 7212, because FOUND has been PUBLISHED on Sriwijaya Law Review VOLUME 3 ISSUE 1, JANUARY 2019 page 1-10 in the online link http://journal.fh.unsri.ac. id / index.php / sriwijayalawreview / article / view / 217 /REVOCATION notices of this article can also be found in Jurisprudence Vol 8 Journal, No. 2 (2018): Vol 8, No 2, December 2018 on http://journals.ums.ac.id/index.php/jurisprudence/article/view/ 7212